Ageism Towards Younger Workers: Prescriptive Stereotypes Among American and Portuguese Workers - Schmitz, S.; Patient, D.; Rosa, M.; Vauclair, C.-M.; Esteves, C. (15th Congress of European Academy of Occupational Health Psychology, 2022)
This research has two main objectives: firstly, to identify prescriptive age stereotypes that younger employees encounter in the workplace and secondly, to compare data from Portugal and the U.S. regarding the content of prescriptive age stereotypes that emerged from the analysis. The average age of the workforce is steadily increasing, and people of different ages are more frequently working side-by-side. This has sparked a greater interest in age in the workplace in general, and age stereotyping and discrimination, in particular. Most ageism (age-based discrimination) research focuses on ageism against older workers, whereas individuals can often be judged not only as too old, but also as too young. To the best of our knowledge, research has not explored prescriptive age stereotypes towards younger workers, i.e., “should”- based expectations that seek to control what members of a certain social group are to do. Macro-level contextual variables, such as cultural values, can influence all levels of stereotyping. Our research used a qualitative approach in two studies (Survey 1 and Survey 2) with independent samples from the U.S. and Portugal: Survey 1 (U.S.: N=69; Portugal: N= 85) examined prescriptive age stereotypes related to younger workers, via open-ended questions about age-based expectations. In order to obtain a contextualized understanding about the manifestation of prescriptive age stereotypes in the workplace, Survey 2 (U.S.: N=77; Portugal: N= 80) asked respondents to bring to mind real-life experiences and observations of stereotyping and ageism against younger workers by using the critical incident technique. Thematic data analysis was based on an inductive approach for Survey 1, and on a deductive approach for Survey 2 by applying the themes that emerged from the analysis of the first survey. After obtaining a satisfactory intercoder agreement level, results showed that, across all samples, the identification of prescriptive age-related stereotypes for younger workers could be organised into 10 overarching themes: Lower status acceptance, Menial tasks acceptance, Technological competence, Professionalism, Openness for learning, Vitality, Loyalty, Nontraditional thinking, Initiative, and Advocating for minimum working conditions. When comparing data from both countries, there were some similarities in the themes that were most often mentioned regarding age-related prescriptive stereotypes ascribed to younger workers, with Openness for learning and Lower status acceptance being mentioned by both the U.S. and the Portuguese samples, and for both Surveys 1 and 2. Yet, there were also some cultural specificities: Advocating for minimum work conditions was only mentioned by the U.S. sample when answering Survey 2, and Acceptance of menial tasks was only mentioned by the Portuguese sample when answering Survey 2. We believe this research contributes to the literature by advancing the understanding of prescriptive age stereotypes against younger workers which is an understudied area. Additionally, these studies are intended to support the development of a scale regarding prescriptive age stereotypes towards younger workers. In terms of practical implications, these studies can inform actions to raise awareness about the consequences of demographic change and of age diversity in the workforce, therefore, helping society to manage more age-diverse groups working together